DNA Sliding Clamps as Therapeutic Targets - Altieri, Amanda S.; Kelman, Zvi (Frontiers in Molecular Biosciences, 2018)
Chromosomal DNA replication is achieved by an assembly of multi-protein complexes at the replication fork. DNA sliding clamps play an important role in this assembly and are essential for cell viability. Inhibitors of bacterial (beta-clamp) and eukaryal DNA clamps (PCNA) have been explored for use as antibacterial and anti-cancer drugs, respectively. Recent inhibitors for bacterial beta clamps include modified peptides (Yin et al., 2013 and Wijffels et al., 2011 and Wolff et al., 2011), small molecule inhibitors RU7 (Georgescu et al., 2008) and compound 4 (Yin et al., 2014b), a natural product, Griselimycin (Kling et al., 2015), and the potential use of modified non-steroidal anti-inflammatory drugs, some of which have nascent antibiotic properties (Yin et al., 2014a). Targeting eukaryotic PCNA sliding clamp in its role in replication can be complicated by undesired effects on healthy cells. Some success was seen in the design of peptide inhibitors ((Gederaas et al., 2014) and (Smith et al., 2015)), however, more recent research has focused on targeting PCNA molecules that are modified in diseased states. (Punchihewa et al, 2012) These inhibitors that are targeted to PCNA involved in DNA repair can sensitize cancer cells to existing anti-cancer therapeutics, such as cisplatin. In very recent work, a DNA aptamer was also shown to inhibit PCNA (Kowalska et al., 2018). In this review, studies in the use of both bacterial and eukaryotic sliding clamps as therapeutic targets are summarized.